THE PREVALENCE OF BLANDM, BLAVIM GENES AMONG ENTEROBACTER CLOACAE BACTERIA - Mahmood, Suhad S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to detect the prevalence of blaVIM and blaNDM genes among Enterobacter cloacae isolates that were isolated from Iraqi patients. About 50 bacterial isolates were collected from different hospitals in Baghdad city and all these isolates were diagnosed using biochemical tests and CHROMagar culture media and conformed using the Vitek II system. The antibiotic susceptibility for E.cloacae isolates  was determined using the disk diffusion (Kirby Bauer) method and the results showed that  these bacteria were showed  resistance to Cefepime and Meropenem antibiotics in percentage (50%), (40%) respectively. In addition it is resistant to Amikacin, ampicillin/sulbactam, Piperacillin, and aztreonam was (20%), (50%), (40%), and (55%) respectively. Also it has been noted that all isolates showed resistance to Cefixime in percentage (100%). EDTA combined disc test was used to detect the ability of E. cloacae isolates to produce carbapenemase and the results were showed that only 8 isolates were gave positive results  , While the prevalence of blaVIM and blaNDM was determined using the conventional Polymerase chain reaction technique.  And the result showed that only four isolates harbored blaNDM while blaVIM was present in 3 isolates